Sistem dan politik ekonomi berjiwa kenyataan - Mubyarto Mubyarto (Economic Journal of Emerging Markets, 1999)
The one of basic weakness of Indonesia economy is its tendency to the haves and strong group more than the poor. This tendency that has deteriorated this current economic crisis occurs because of capital system implemented by Indonesia. So, Indonesia has to develop a people centered economy, both on its system and politics. This paper discusses the people centered economy in relation with some actual economic issues, ie : democracy of economic corruption - collusion - nepotism (KKN), free trade, formal sector, regional autonomy, and poverty.